2010 IEEE International Reliability Physics Symposium 2010
DOI: 10.1109/irps.2010.5488859
|View full text |Cite
|
Sign up to set email alerts
|

The time dependent defect spectroscopy (TDDS) for the characterization of the bias temperature instability

Abstract: We introduce a new method to analyze the statistical properties of the defects responsible for the ubiquitous recovery behavior following negative bias temperature stress, which we term time dependent defect spectroscopy (TDDS). The TDDS relies on small-area metaloxide-semiconductor field effect transistors (MOSFETs) where recovery proceeds in discrete steps. Contrary to techniques for the analysis of random telegraph noise (RTN), which only allow to monitor the defect behavior in a rather narrow window, the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
222
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(243 citation statements)
references
References 29 publications
14
222
1
1
Order By: Relevance
“…We study the duty-factor and frequency dependence in the light of the recently proposed capture/emission time (CET) map model [7,[21][22][23] and demonstrate that the recoverable component of BTI can only to the first-order be captured by a two-state defect model. By using a three-state defect model, consistent with detailed studies on the microscopic defect properties [24,25], the experimentally observed frequency dependence can be reproduced for a wide range of technologies.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…We study the duty-factor and frequency dependence in the light of the recently proposed capture/emission time (CET) map model [7,[21][22][23] and demonstrate that the recoverable component of BTI can only to the first-order be captured by a two-state defect model. By using a three-state defect model, consistent with detailed studies on the microscopic defect properties [24,25], the experimentally observed frequency dependence can be reproduced for a wide range of technologies.…”
Section: Introductionmentioning
confidence: 67%
“…Note, however, that the effective time constants in the CET map do not directly correspond to physical defect parameters like thermodynamic energy-levels or relaxation energies but are functions of them [27]. In this sense we wish to highlight that the CET map model is not a new model meant to replace our previous modeling efforts such as [24,31]. Rather, the CET map model provides a convenient transformation of the experimental data to help understand the wide distribution of time constants.…”
Section: Capture/emission Time Map Model For Btimentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this empirical parameter is needed to reproduce single defects experiment results where the capture rates are evaluated from variation of electrical parameters and indicate a smaller dependence than exponential with the field [23]. Additional studies based on time dependent defect spectroscopy (TDDS) in [24] show how this behavior can reach saturation at higher stress voltages. Huard [23] showed that a constant critical field of 3 MV/cm agrees well with the capture rates exponential dependence measured over different CMOS technologies.…”
Section: Model Description and Validationmentioning
confidence: 99%
“….Þ have been taken from measurement values based on scanning tunneling spectroscopy studies for single-defect Si dangling bonds [25]. The dynamics of other oxide traps (E c and E d [7,32]) are better described including metastable states [11,24]. However, EPR studies indicated that these defects relax almost immediately after the removal of the stress condition [9], and thus they have not been investigated in this study.…”
Section: Model Description and Validationmentioning
confidence: 99%